Study on the Interaction of Bovine Serum Albumin with Ceftriaxone and the Inhibition Effect of Zinc (II). (15th July 2012) - Yue, Qiaoli; Shen, Tongfei; Wang, Changna; Gao, Chaohui; Liu, Jifeng
Abstract : The mechanism of the interaction between bovine serum albumin (BSA) and ceftriaxone with and without zinc (II) (Zn 2+ ) was studied employing fluorescence, ultraviolet (UV) absorption, circular dichroism (CD), and synchronous fluorescence spectral methods. The intrinsic fluorescence of BSA was quenched by ceftriaxone in a static quenching mode, which was authenticated by Stern-Volmer calculations. The binding constant, the number of binding sites, and the thermodynamic parameters were obtained, which indicated a spontaneous and hydrophobic interaction between BSA and ceftriaxone regardless of Zn 2+ . Changes in UV absorption, CD, and synchronous fluorescence spectral data are due to the microenvironment of amide moieties in BSA molecules. In the BSA-ceftriaxone-Zn 2+ system, Zn 2+ must first interact with ceftriaxone forming a complex, which inhibits BSA binding to ceftriaxone. The present work uses spectroscopy to elucidate the mechanism behind the interaction between BSA and ceftriaxone in the presence and absence of Zn 2+ . The BSA and ceftriaxone complex provides a model for studying drug-protein interactions and thus may further facilitate the study of drug metabolism and transportation.